Coping with an Uncertain Future: Religiosity and Millenarianism - Zwingmann, Christian; Murken, Sebastian (Archive for the psychology of religion, 2000)
In a variety of ways, religiosity can help maintain or restore one's future capacity to act. Broadening the coping perspective for the psychology of religion (Pargament, 1997) seems to be an adequate theoretical framework for a differentiated analysis of who uses religiosity at what point, in what manner, and with which kind of outcomes in the process of coping with the future. We will introduce this approach and summarize the empirical results that are available up to now. Subsequently, we will be occupied with religious cognitions about the future in a narrower sense: with the so-called millenarian or chiliastic ideas of some religious communities about the imminent end of this world. First, we will work out the specific criteria of such cognitions. Based on the approach of religious coping we will then examine whether millenarianism can be helpful in coping with the future. Our functional analysis proposes that central elements of chiliastic ideas serve to convince the believer that his life has meaning and purpose despite the obvious suffering and evil in the world. However, specific difficulties and risks are intertwined with chiliastic forms of coping with the future, namely: the derogation of this world, the problems arising from a prediction of explicit dates for the end of the world, and the connection between millenarianism and violence.